DISTRIBUSI RUANG TERBUKA HIJAU (RTH) DI LINGKUNGAN POLITEKNIK NEGERI SEMARANG, KOTA SEMARANG: DISTRIBUSI RUANG TERBUKA HIJAU (RTH) DI LINGKUNGAN POLITEKNIK NEGERI SEMARANG, KOTA SEMARANG - Pangesti, Rendy Dwi; Sulistiawati, Baiq Heny; Goro, Garup Lambang; Junaidi; Imansyah, Salmaa R.N.; A.U., Akhmad Daffa’ (Bangun Rekaprima, 2026)
Ruang Terbuka Hijau (RTH) plays an important role in maintaining environmental quality and enhancing comfort within educational areas; therefore, an evaluation of existing conditions and optimization strategies is required at Politeknik Negeri Semarang. This study aims to map and analyze the area and spatial distribution of RTH using field surveys and data processing based on Geographic Information Systems (GIS). The results show that the total area of Politeknik Negeri Semarang is 111,251 m², with RTH covering 19,086.1 m² or 17.16% of the total area. Although this proportion meets the minimum requirement for private green open space, it remains below the ideal standard of 30%. The uneven distribution of RTH and variations in vegetation quality indicate the need for optimization through the utilization of potential land and improvement of green space quality. This study concludes that RTH is an effective decision-support tool for sustainable planning and management of green open space.